HUBUNGAN SMARTPHONE ADDICTION DENGAN KECEMASAN SOSIAL PADA REMAJA - Reza Indra Wiguna; Lalu Hersika Asmawariza; Raihana Qolbi; Vera Yulandasari (Jurnal Ilmu Keperawatan Komunitas, 2024)
Smartphone users globally account for 67.1% of the world's total population, while in Indonesia they account for 73.7% of the total population. Excessive use of smartphones have a negative impact on individuals, one of which is social anxiety. Social anxiety is a feeling of discomfort when dealing with social situations. The purpose of this study was to determine the relationship between smartphone addiction and social anxiety in adolescents in Jenggik Village, Terara Health Center Working Area. This study used a quantitative approach with a correlational design and cross-sectional approach. The study population was all teenagers in Jenggik Village and the sample amounted to 94 people who were taken using the slovin formula with simple random sampling technique. The data collection method used the SAS-SV and SAS-A questionnaires. Data analysis used spearman rank correlation analysis. The results showed that there was a relationship between smartphone addiction and social anxiety with a p-value of 0.000 <0.05. The direction of the relationship is positive with moderate relationship strength. Respondents who experience smartphone addiction and social anxiety are dominated by women, this can occur because women are more concerned about appearance and trends, less able to think positively in their interpretations when interacting.